Exploring Urban Slum Education Through Photovoice With Children: Concepts and Techniques for Research - InJung Cho (Journal of Participatory Research Methods)
Despite the expanding population of children in urban slums, the strive to ensure equitable education remains an under-appreciated and under-developed area. Yet, more research on urban slum education is necessary as urban slums are not merely physical spaces, but they portray multifaceted sociocultural issues in education. Conducting photovoice with children in slums is conducive to building a comprehensive and contextualized understanding of urban slum education based on children’s perspectives. What concepts of urban slum education can researchers explore and how can photovoice help researchers understand them? In what ways can researchers adopt photovoice to explore the educational experiences of slum children by centering children’s perspectives? This paper discusses five concepts of urban slum education, followed by each photovoice technique to explore them effectively. Further, this study provides technical issues for researchers to ensure that their research empowers children and is culturally relevant. The resulting comprehensive understanding of urban slum education will contribute to the development of slum-specific curricula and education policies and programs that are aligned with children’s best interests.